A two‐path model of auditory modulation detection using temporal fine structure and envelope cues. (12th February 2018) - Ewert, Stephan D.; Paraouty, Nihaad; Lorenzi, Christian
Abstract: A model using temporal‐envelope cues was previously developed to explain perceptual interference effects between amplitude modulation and frequency modulation (FM). As that model could not accurately predict FM sensitivity and the interference effects, temporal fine structure (TFS) cues were added to the model. Thus, following the initial stage of the model consisting of a linear filter bank simulating cochlear filtering, processing was split into an 'envelope path' based on envelope power cues and a 'TFS path' based on a measure of the distribution of time intervals between successive zero‐crossings. This yielded independent detectability indices for envelope and TFS cues, which were optimally combined to produce a single decision statistic. Independent internal noises in the envelope and TFS paths were adjusted to match the data. Simulations indicate that TFS cues are required to account for FM data for young normal‐hearing listeners and that TFS processing is impaired for both older normal‐hearing and hearing‐impaired listeners. The role of TFS was further assessed by relating the monaural FM sensitivity to measures of interaural phase difference, commonly assumed to rely on binaural TFS sensitivity. The model demonstrates that binaural TFS sensitivity is considerably lower than monaural TFS sensitivity. Similar to FM thresholds, interaural phase difference sensitivity declined with age and hearing loss, although higher degradations were observed in binaural temporal processing compared to monaural processing. Overall, this model provides a novel tool to explore the mechanisms involved in FM processing in the normal auditory system and the degradations in FM sensitivity with ageing and hearing loss. Abstract : A two‐path model using envelope and temporal fine structure (TFS) cues was developed to explain perceptual interference effects between amplitude modulation and frequency modulation (FM) in normal‐hearing and hearing‐impaired listeners. The model demonstrates that binaural TFS sensitivity is considerably lower than monaural TFS sensitivity. The model provides a tool to explore the mechanisms involved in FM processing in the normal auditory system and the degradations in FM sensitivity with ageing and hearing loss.